Common Requirement for the Relaxosome of Plasmid R1 in Multiple Activities of the Conjugative Type IV Secretion System - Lang, Silvia (American Society for Microbiology, 2014)
Macromolecular transport by bacterial type IV secretion systems involves regulated uptake of (nucleo)protein complexes by the cell envelope-spanning transport channel. A coupling protein receptor is believed to recognize the specific proteins destined for transfer, but the steps initiating their translocation remain unknown. Here, we investigate the contribution of a complex of transfer initiation proteins, the relaxosome, of plasmid R1 to translocation of competing transferable substrates from mobilizable plasmids ColE1 and CloDF13 or the bacteriophage R17. We found that not only does the R1 translocation machinery engage the R1 relaxosome during conjugative self-transfer and during infection by R17 phage but it is also activated by its cognate relaxosome to mediate the export of an alternative plasmid. Transporter activity was optimized by the R1 relaxosome even when this complex itself could not be transferred, i.e., when the N-terminal activation domain (amino acids 1 to 992 [N(1-992)]) of TraI was present without the C-terminal conjugative helicase domain. We propose that the functional dependence of the transfer machinery on the R1 relaxosome for initiating translocation ensures that dissemination of heterologous plasmids does not occur at the expense of self-transfer.